2018
DOI: 10.1111/jfs.12467
|View full text |Cite
|
Sign up to set email alerts
|

Advanced meat preservation methods: A mini review

Abstract: Development of various novel thermal and nonthermal techniques has shown potential applications in meat processing and preservation. Consumer's demand of meat products with esteemed quality, wholesomeness, and superior safety has led to the commercial introduction of these innovative methods. Accordingly, this treatise outlines the potential of several advanced thermal and nonthermal methods like super‐chilling, ultrarapid freezing, immersion vacuum cooling, hydrofluidization freezing, impingement freezing, el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 54 publications
1
33
0
Order By: Relevance
“…TEM images revealed that the particle size of liposomes under probe-type ultrasonication was also significantly smaller than that under ultrasonic bath and magnet stirring. Increasing temperature and homogenization intensity resulted in decreased liposome particle size, with similar results reported by other studies (Justo & Moraes, 2011;Rahman et al, 2018).…”
Section: F I G U R E 3 Effect Of Temperatures During the Extraction Osupporting
confidence: 90%
See 3 more Smart Citations
“…TEM images revealed that the particle size of liposomes under probe-type ultrasonication was also significantly smaller than that under ultrasonic bath and magnet stirring. Increasing temperature and homogenization intensity resulted in decreased liposome particle size, with similar results reported by other studies (Justo & Moraes, 2011;Rahman et al, 2018).…”
Section: F I G U R E 3 Effect Of Temperatures During the Extraction Osupporting
confidence: 90%
“…The particle size and PDI of liposomes prepared by the ethanol injection technique can be controlled by a number of parameters, such as lipid concentration and composition, concentration and type of encapsulated drug, injection rate, temperature, and homogenization intensity (Rahman et al, 2018). Because the transition temperature (Tc) of soybean lecithin was 50.4 C, higher than Tc, it may result in the reduction of biological activity and structural changes (Rahman et al, 2018). For that reason, the experiments in this study were carried out in the temperature range from 30 to 50 C. Furthermore, three common homogenization methods (magnet stirring, ultrasonic bath, and probe-type ultrasonication) were also investigated in this experiment.…”
Section: Physical Characterization Of Liposomesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many techniques have been employed in lab-scale liposome preparation and drug loading, but only a few large-scale techniques (ethanol injection and supercritical fluid process) are available. High-pressure processing (HPP) was officially recognized by the U.S. Food and Drug Administration in 2000 and is a non-thermal pasteurization technology that uses hydrostatic pressure rather than the conventional method of heat to destroy microorganisms in the food industry [ 12 ]. Laboratory HPP equipment with different capacities from 0.3 to 10 L have been developed by the supplier (Avure, Stansted Fluid Power, Baotou, Kobelco, and Toyo Koatsu).…”
Section: Introductionmentioning
confidence: 99%